A Fabrication Strategy for Reconfigurable Millimeter‐Scale Metamaterials. (16th August 2021) - McClintock, Hayley D.; Doshi, Neel; Iniguez‐Rabago, Agustin; Weaver, James C.; Jafferis, Noah T.; Jayaram, Kaushik; Wood, Robert J.; Overvelde, Johannes T. B.
Abstract: Rather than depending on material composition to primarily dictate performance metrics, metamaterials can leverage geometry to achieve specific properties of interest. For example, reconfigurable metamaterials have enabled programmable shape transformations, tunable mechanical properties, and energy absorption. While several methods exist to fabricate such structures, they often place severe restrictions on manufacturing materials, or require significant manual assembly. Moreover, these arrays are typically composed of unit cells that are either macro‐scale or micro‐scale in dimension. Here, the fabrication gap is bridged, and laminate manufacturing is used to develop a method for designing reconfigurable metamaterials at the millimeter‐scale, that is compatible with a wide range of materials, and that requires minimal manual assembly. In addition to showing the versatility of this fabrication method, how the use of laminate manufacturing affects the behavior of these multi‐component arrays is also characterized. To this end, a numerical model that captures the deformations exhibited by the structures is developed, and an analytic model that predicts the strain of the structure under compressive stress is built. Overall, this approach can be leveraged to develop millimeter‐scale metamaterials for applications that require reconfigurable materials, such as in the design of tunable acoustics, photonic waveguides, and electromagnetic devices. Abstract : Laminate fabrication is used to design reconfigurable millimeter‐scale metamaterials from a wide range of materials with minimal manual assembly. Numerical and analytical models are built to predict the deformation modes of the array and the properties of the structure under compression. This approach will enable the development of structures that require reconfiguration, including tunable acoustic dampeners, photonic waveguides, and electromagnetic devices.